Is Lipid Profile Associated with Bone Mineral Density and Bone Formation in Subjects with Spinal Cord Injury?. (21st August 2014) - Sabour, Hadis; Norouzi Javidan, Abbas; Latifi, Sahar; Hadian, Mohammad Reza; Emami Razavi, Seyed-Hassan; Shidfar, Farzad; Vafa, Mohammad Reza; Aghaei Meybodi, Hamidreza
Abstract : Purpose . The association between serum lipids and bone mineral density (BMD) has been investigated previously but, up to now, these relationships have not yet been described in spinal cord injury (SCI). We tried to assess the correlation between serum triglyceride (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) and BMD in male subjects with SCI. Methods . Dual-energy X-ray absorptiometry (DXA) was used to assess BMD in femoral neck, trochanter, intertrochanteric zone, and lumbar vertebras. Blood samples were taken to measure serums lipids and bone biomarkers including osteocalcin, cross-linked type I collagen (CTX), and bone alkaline phosphatase (BALP). Partial correlation analysis was used to evaluate the relationships between mentioned measurements after adjustment for weight and age. Results . We found a positive correlation between HDL and femoral neck BMD (P : 0.004, r = 0.33 ). HDL was negatively correlated with osteocalcin (P : 0.017, r = - 0.31 ) which was not in consistency with its relationship with BMD. TC and LDL were not related to CTX, BALP and BMD. Conclusion . This study does not support a strong association between serum lipids and BMD in subjects with SCI. Moreover it seems that positive association between HDL and BMD is not mediated through increased bone formation.